P‐99: Method to Reduce Ringing Artifact in Holographic Projection. Issue 1 (29th May 2019) - Chen, Chun; Xiao, Dan; Liu, Chan-Juan; Wang, Jun; Wang, Qiong-Hua
Abstract : A method to reduce the ringing artifact in the holographic projection is proposed in this paper. By reducing the distance between the focal plane and the hologram plane and keeping the focal length of the convergence light unchanged in random phase‐free method, the ringing artifacts can be reduced.